Targeted delivery of CD44s-siRNA by ScFv overcomes de novo resistance to cetuximab in triple negative breast cancer. (July 2018) - Fu, Wenyan; Sun, Hefen; Zhao, Yang; Chen, Mengting; Yang, Lipeng; Yang, Xueli; Jin, Wei
Highlights: CD44 mediated EGFR-degradation impairment is responsible for cetuximab resistance in triple negative breast cancers. SiRNAs targeting CD44s resensitize TNBC cells to respond to cetuximab. A ScFv-tp fusion protein generated from cetuximab and truncated protamine shows similar biological characterization as anti-EGFR antibody. EGFR targeting ScFv-tp-siRNA complex is shown to notably inhibit cetuximab-resistant TNBC tumors both in vitro and in vivo . Abstract: The overexpression of EGFR often occurs in TNBC, and the anti-EGFR receptor antibody cetuximab is used widely to treat metastatic cancer in the clinic. However, EGFR-targeted therapies have been developed for TNBC without clinical success. In this study, we show that impaired EGFR degradation is crucial for resistance to cetuximab, which depends on the cell surface molecule CD44. To further investigate the role of CD44 in EGFR signaling and its treatment potential, we developed a targeting fusion protein composed of an anti-EGFR scFv generated from cetuximab and truncated protamine, called Ce-tP. CD44 siRNA can be specifically delivered into EGFR-positive TNBC cells by Ce-tP. Efficient knockdown of CD44 and suppression of both EGFR and downstream signaling by the Ce-tP/siRNA complex were observed in EGFR-positive TNBC cells. More importantly, our results also showed that targeted delivery of siRNA specific for CD44 can efficiently overcome resistance to EGFR targeting in TNBC cells both in vitro and in vivo . Overall, our results establish a new principle to achieve EGFR inhibition in TNBC and limit drug resistance.